2012
DOI: 10.1542/peds.2011-1714
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Net Cost of Reminder/Recall for Adolescent Immunizations

Abstract: R/R was successful at increasing immunization rates in adolescents and effect sizes were comparable to those in younger children. Practices conducting R/R may benefit financially if they can generate additional well-child care visits and keep supply costs low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 23 publications
1
94
2
Order By: Relevance
“…Importantly, the cost per additional adolescent vaccinated was higher than the cost per additional individual vaccinated reported in some studies [50][51][52] but in the range of other studies 17,53 and less than the costs for stepped reminder/outreach interventions 27,28 ; also the benefits involved both improved immunizations and greater preventive care visits.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Importantly, the cost per additional adolescent vaccinated was higher than the cost per additional individual vaccinated reported in some studies [50][51][52] but in the range of other studies 17,53 and less than the costs for stepped reminder/outreach interventions 27,28 ; also the benefits involved both improved immunizations and greater preventive care visits.…”
Section: Discussionmentioning
confidence: 73%
“…13,14 Nevertheless, little evidence exists for the effectiveness of practice-based reminder/recall for adolescent immunizations, 15,16 although in one recent study in 4 practices researchers demonstrated increased immunization rates. 17 Moreover, few practices actually use reminder/recall for patients of any age [18][19][20] ; barriers include the added workload, costs, and complexities of conducting such a program. 21,22 Furthermore, some recent studies targeting low-income populations found little or no benefit to practice-based reminder/recall for young children because of difficulties in reaching families that often change addresses or telephone numbers.…”
Section: Introductionmentioning
confidence: 99%
“…55,56 The positive effect of our dose 2 and 3 telephone recalls on improving completion corresponds with other studies of urban, underserved adolescent populations. 21,23,57,58 Only 5% to 25% of US pediatric practices use reminder/recall interventions. 59,60 Key implementation barriers include lack of human and financial resources, low confidence that immunization histories are up-to-date, and need for accurate contact information.…”
Section: Discussionmentioning
confidence: 99%
“…28 The results of these studies underscore the importance of reliable contact information as a prerequisite for effective family-focused intervention.…”
Section: Articlementioning
confidence: 93%
“…In addition, although basic reminder calls to families have proven effective in fostering vaccination, 26 only 2 studies of reminder calls for adolescent vaccination have been published, revealing mixed results. 27,28 Although CDS has been defined as including alerts to clinicians or families, 29 researchers have not conducted large-scale trials of automated, EHR-based decision support directed at both clinicians and families in any context. Given multiple family and clinician barriers to HPV vaccination, this strategy may better address obstacles to vaccine receipt than either family-focused or CDS alone.…”
mentioning
confidence: 99%